Uso da terra e qualidade da água da bacia hidrográfica do Arroio Ribeirão, São Pedro do Sul/RS - Oliveira, Mariana Xavier de (2014)
Human activities has exerted deep, and commonly, negative influence on water bodies, and some of these effects are due to pollutants, others due to misuse of land by humans, or even by poor soil management by society. The study of human activities and their influences on the water quality presupposes that water bodies has the ability to reflect amendments in their properties due to human activities on the strands surface that compose the watershed. The knowledge of the characteristics about to water quality and land use in a watershed is of utmost importance, because every form of use implemented influences direct and indirect on the quality and disposition of water resources.So, the general objective of this work was to study the watershed of the arroio Ribeirão in Sao Pedro do Sul / RS, emphasizing environmental problems, especially degradation of the aquatic environment and surface erosion. The methodology used was based by the deductive method. Marconi and Lakatos (2010, p.74) assert that "deductive arguments sacrifice the enlargement the content to achieve the" certainty". This method takes into account the scientific knowledge as being sort of controlled speculation, and that does not require the researcher starts working by hypotheses and observation of facts, but by theory or models (CHRISTOFOLETTI, 1999).The present research was divided into two stages: cabinet step and field step. Seeking to organize the procedures that came to compose the cabinet research was elaborated the bibliographic review on the matters that concern: environmental quality, water quality, geomorphology and environmental legislation. In the field stage were conducted in the fall (06/20/2013) and spring (06/10/2013) where were collected on two occasions, water samples for the achievement of the CE, pH, TSD tests and water temperature , at second field were conducted the resistance test to the penetration to infer the surface erosion. As a result, it was observed that the main land uses are tillage and field, destined to planting rice, corn and pastures and relating itself directly with the maintenance of the resident population in the field and also forest in the sloping areas; the insolation and amount of water available are the main conditioners to factor water temperature, as was anticipated; in the cold seasons, the land use combined with forest and tillage increase the rate of CE, which does not occur in the warm seasons; In the cold seasons the pH rates decrease, coming to be below the minimum index type recommended for human needs, which does not occur in the warm seasons where rates rise, both in the warm seasons as cold, rates of TSD in the arroio Ribeirão are within the recommended limits for human consumption; the margins of the main river are outside of the current legislation, having no riparian vegetation 30 meters of these margins; There is a possibility of occurrences of surface erosion at all points where the penetration resistance tests were performed, because in all of them there is an indication of subsurface compaction indicating that if the saturation of the upper soil , this can be removed by leaching. In this sense, it is worth emphasizing that besides data produced by this research are required other complementary surveys that encompass other focus of activity in the environment line, for example, studies that consider the socio-economic, cultural and educational aspects, since they present relationship with the intensity of consumption, greater or lesser degree of environmental conscience and even the form of intervention in the natural environment.